Hedonic response sensitivity to variations in the evaluation task and culinary preparation in a natural consumption context - Galiñanes Plaza, Adriana; Saulais, Laure; Delarue, Julien (Frontiers in Nutrition, 2022)
Hedonic measurements in the frame of consumer tests of foods are prone to many different biases and the validity of test designs has been subject to much research with special emphasis on the role of context. While bringing elements of natural consumption context to the testing conditions is generally seen as an improvement, other aspects of the test design such as the task format have received little attention. In particular, the influence of analytical questions on hedonic responses has been studied in standardized contexts only. This study aimed to assess whether synthetic and analytical evaluation tasks result in different hedonic responses when the test is conducted in a natural consumption context. Bread and pizzas with different degrees of culinary preparation (homemade, readymade, and a combination of the two) were tested on three separate days in a university cafeteria. Overall liking scores of the bread and the three different pizzas were obtained either with a synthetic (hedonic question only) or with an analytical task (hedonic question plus intensity attributes). Care was taken to avoid any other changes to normal eating conditions, notably by recruiting on the spot only those customers who had spontaneously chosen pizza as part of their lunch. Liking scores of the homemade pizza were lower with the analytical task while the scores of the other two pizzas did not change significantly. Moreover, different rankings of the pizzas were obtained when the data were analyzed separately for each evaluation task format. The synthetic evaluation task would have led to the conclusion that the homemade pizza was the best liked and the readymade being the least liked, while the analytical evaluation task would have led to the conclusion that the ‘mixed’ pizza would be liked significantly more than the other two. The effect of the task format (i.e. lower scores with the analytical task) was more pronounced when participants reported they had spent more time in the queue. These results strengthen the view that the task is part of the evaluation context and must be carefully considered when one wishes to design ecologically valid consumer tests.